2020
DOI: 10.1371/journal.pone.0221742
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assays to detect the presence and viability of Phytophthora ramorum and Grosmannia clavigera

Abstract: Wood and wood products can harbor microorganisms that can raise phytosanitary concerns in countries importing or exporting these products. To evaluate the efficacy of wood treatment on the survival of microorganisms of phytosanitary concern the method of choice is to grow microbes in petri dishes for subsequent identification. However, some plant pathogens are difficult or impossible to grow in axenic cultures. A molecular methodology capable of detecting living fungi and fungus-like organisms in situ can prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…A further hypothesis is that the drawing came into contact with furniture or woody material, possibly raw, contaminated by the fungus. The DNA in G. clavigera mycelium remains stable for more than 10 years also in heat-treated wood samples (Wong et al, 2020). Finally, the genus Trichoderma was present in L7 and L8, with the species T. reesei as the dominant species in both drawings.…”
Section: Fungimentioning
confidence: 90%
“…A further hypothesis is that the drawing came into contact with furniture or woody material, possibly raw, contaminated by the fungus. The DNA in G. clavigera mycelium remains stable for more than 10 years also in heat-treated wood samples (Wong et al, 2020). Finally, the genus Trichoderma was present in L7 and L8, with the species T. reesei as the dominant species in both drawings.…”
Section: Fungimentioning
confidence: 90%
“…580 Sordariomycetes genome assemblies (one reference genome per species) were downloaded from NCBI (21/05/2021), the two assemblies were downloaded from JGI Mycocosm ( S. kochii, T. guianense ), and two from other resources ( O. ulmi W9 (Christendat, 2013), L. longiclavatum ( Wong et al, 2020 )). All assemblies were filtered for short contigs (< 1000 bp) and contaminants as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, we used gapdh transcript levels as a surrogate readout for cell viability. Previous studies have used mRNA to estimate cell viability within a population in vitro ( Wong et al., 2020 ; Collins et al., 2022 ). We showed that there were no significant differences ( p >0.05) in the gapdh cycle threshold value between mRNA obtained from an equal number of DaFucTA2 silenced or control cells ( Supplementary Figure 2 ) indicating a similar number of viable cells was present in each treatment group.…”
Section: Discussionmentioning
confidence: 99%